Illness perception as a predictor of health-related quality of life in patients with end stage renal disease: comparison between haemodialysis and continuous ambulatory peritoneal dialysis patients - Norhayati Ibrahim; Norella Kong Chiew Thong; Asmawati Desa; Rozmi Ismail (Universiti Kebangsaan Malaysia, 2015)
This cross-sectional study examined the influence of illness perception of health-related quality of life (HRQoL) in end stage renal disease (ESRD) patients on either hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD). The Short Form-36 (SF-36) was used to measure HRQoL which comprised the Physical Component Summary (PCS) and Mental Component Summary (MCS). Illness perception was evaluated using Revised Illness Perception Questionnaire (IPQ-R). Both questionnaires were administered on 183 HD and 93 CAPD patients. The results showed that almost all HRQoL subscales except physical functioning and bodily pain were found to be significantly different between HD and CAPD patients. There are significant correlations between most components of illness perception with HRQoL. Significant illness perception predictors of PCS among HD patients were time line, consequences, cyclical and identity, whereas on CAPD patients were time line, illness coherence, emotional, cyclical and identity. Significant illness perception predictors of MCS among HD patients included time line, cyclical and identity and only time line was significant predictor of MCS on CAPD patients. These should be considered when developing intervention programmes to improve their HRQoL.